Studies of Intra-Fraction Prostate Motion During Stereotactic Irradiation in First Irradiation and Re-Irradiation - Taillez, Alexandre; Bimbai, Andre-Michel; Lacornerie, Thomas; Le Deley, Marie-Cecile; Lartigau, Eric F.; Pasquier, David (Frontiers in Oncology, 2021)
Background: Understanding intra-fractional prostate motions is crucial for stereotactic body radiation therapy (SBRT). No studies have focused on the intra-fractional prostate motions during re-irradiation with SBRT. The objective was to evaluate these translational and rotational motions in primary treated patients and in the context of re-irradiation. Methods: From January 2011 to March 2020, 162 patients with histologically proven prostate cancer underwent prostate SBRT, including 58 as part of a re-irradiation treatment. We used the continuous coordinates of the fiducial markers collected by an orthogonal X-ray dual-image monitoring system. The translations and rotations of the prostate were calculated. Prostate deviations representing overall movement was defined as the length of the 3D-vectors. Results: A total of 858 data files were analyzed. The deviations over time in the group of primary treated patients were significantly larger than that of the group of re-irradiation, leading to a mean deviation of 2.73 mm (SD =1.00) versus 1.90 mm (SD =0.79), P<0.001. In the re-irradiation group, we identified displacements of -0.05 mm (SD =1.53); 0.20 mm (SD =1.46), and 0.42 mm (SD =1.24) in the left-right, superior-inferior and anterior-posterior planes. Overall, we observed increasing deviations over the first 30 min followed by a stabilization related to movements in the three translational axes. Conclusion: This is the first study to focus on intrafraction prostate motions in the context of re-irradiation. We observed that intra-fraction prostate motions persisted in the setting of re-irradiation, although they showed a significant reduction when compared with the first irradiation. These results will help to better estimate random errors during SBRT treatment of intra-prostatic recurrence after irradiation.